The risk-taking channel of monetary policy - Bonfim, Diana (2022)
The literature on the risk-taking channel of monetary policy grew quickly, leading to scattered evidence. We examine this channel through different angles, exploring detailed information on loan origination and performance. Ex ante riskier borrowers receive more funding at the extensive margin when interest rates are lower. Ex post performance is independent of the level of interest rates at origination. Still, loans granted in periods of very low and stable interest rates show higher default rates once interest rates start to increase. Risk-taking is stronger among banks with lower capital ratios, suggesting that this channel may be linked to managerial incentives for risk-shifting.